2005
DOI: 10.1096/fj.05-4031fje
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 inhibits calcium transients in bovine trachealis cells by a ryanodine receptor dependent mechanism

Abstract: IL-4 and IL-13 have important roles in the pathogenesis of asthma. A novel finding was that brief exposure of airway smooth muscle cells to IL-4 inhibited carbachol-stimulated calcium transients. We hypothesized that IL-4 inhibits transients by decreasing calcium store content and tested this by measuring the effects of IL-4 on transients induced by a nonspecific ionophore. Bovine trachealis cells were loaded with fura 2-AM, and cytosolic calcium concentrations ([Ca2+]i) were measured in single cells by digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
(68 reference statements)
2
10
0
Order By: Relevance
“…release of Ca 2+ through RyR leads to activation of K + channels, membrane hyperpolarisation and closure of voltage-dependent Ca 2+ channels. In the present study, isoproterenol did appear to promote Ca 2+ release through RyR (figs 6 and 7); this was also documented using the nitric oxide donor SNAP [32], and the same response was found upon stimulation with isoproterenol [13] and interleukin-4 [12]. Nonetheless, contraction of ASM is normally poorly dependent upon electromechanical coupling and, in the present study, the bronchodilatory action of isoproterenol was found to be largely unaffected by inhibition of RyR.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…release of Ca 2+ through RyR leads to activation of K + channels, membrane hyperpolarisation and closure of voltage-dependent Ca 2+ channels. In the present study, isoproterenol did appear to promote Ca 2+ release through RyR (figs 6 and 7); this was also documented using the nitric oxide donor SNAP [32], and the same response was found upon stimulation with isoproterenol [13] and interleukin-4 [12]. Nonetheless, contraction of ASM is normally poorly dependent upon electromechanical coupling and, in the present study, the bronchodilatory action of isoproterenol was found to be largely unaffected by inhibition of RyR.…”
Section: Discussionsupporting
confidence: 83%
“…The role of RyR in ASM in particular is still not entirely clear, with some proposing its importance in bronchoconstriction [3,[6][7][8][9][10][11] or in bronchodilation [12,13], and others finding no detectable role [14]. In the present study, the role of RyR in human and bovine ASM was investigated using Ca…”
Section: +mentioning
confidence: 94%
“…The IL-4 concentrations used during this study were similar to those employed in previous in vitro studies (10-50 ng/ml). 61,62 In a model of IL-4-induced rat hepatitis, IL-4 serum concentrations reached 1800 pg/ml. 63 In HIV-Trypanosoma cruzi coinfection, IL-4 serum levels reached 6200 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The IL‐4 concentrations used here were similar to those used in previous in vitro studies (50 ng/ml; refs. 27, 51), although no information is available on IL‐4 concentrations in liver or serum after liver transplantation. In a model of rat hepatitis induced by IL‐4, the IL‐4 serum concentration reached 1800 pg/ml (52).…”
Section: Discussionmentioning
confidence: 99%